AUDIO CLIPS IN DEVELOPING LISTENING COMPREHENSION SKILLS IN MALAYSIAN PRIMARY ESL CLASSROOMS - Choo Siang Shian; Melor Md. Yunus (Proceedings of The ICECRS, 2016)
Listening skill has been an under-emphasised skill in many English as a Second Language (ESL) classrooms until recent decades. To keep up with the global advancement of technology, many studies on listening skills have integrated use of technology. In Malaysia, listening skills are also often neglected due to the highly examination-oriented education system. Since communication and technology competence are important 21st century skills, learners should be exposed to listening skills using no less than multimedia, especially when technology is inaccessible in rural parts of the country. This paper aims to examine the perceptions of teachers and pupils in using audio clips to develop listening comprehension skills in a rural primary school in Sarawak, East Malaysia, where digital facilities and internet connection are lacking in many parts of the state. Focus group interviews were conducted with two teachers and three ESL pupils after six weekly listening activities using audio clips based on the textbooks. Findings indicated that the teachers found audio clips to be useful and convenient, while pupils exhibited more interest and concentration during lessons. All respondents believed that audio clips could encourage the development of listening comprehension skills. Finally, it is recommended that audio clips could be expanded into a listening module that slowly moves towards authentic listening to equip learners with real-world skills and experiences.